Hipercorreção na escrita acadêmica: uma análise de textos de alunos da graduação em direito - Juliana dos Santos Belga (2019)
Hypercorrection occurs when language users, whether in spoken or written language, produce incorrect word forms and expressions from the gramatical point of view with the intention of reaching the standard language. Generally, this phenomenon occurs by analogy to rules already learned and it is recurring with words that are subject to correction, especially by the school. Based on this principle, under the theoretical perspectives of Sociolinguistics and Educational Sociolinguistics, this research had the corpus constituted by non-probabilistic sampling. The objective of this study was to describe the phenomenon of hypercorrection in the texts written by undergraduate students in Law so that it was possible to identify aspects that characterize this phenomenon, to conceptualize hypercorrection in writing, check your most recurring types, examine the factors that influence it and finally to reflect about possible pedagogical practices. The data analysis, carried out on the basis of qualitative principles, showed that hypercorrection in academic writing occurs mainly at the orthographic and stylistic levels and revealed the little familiarity of students with formal writing. The results point out to the need of continuous work with the text production, from elementary school to university education, that allows students to become aware of the writing process, to effectively learn the orthographic and grammatical rules, to improve written interaction in the academic environment, professional and in the several social practices.